2016
DOI: 10.1186/s12885-016-2952-3
|View full text |Cite
|
Sign up to set email alerts
|

Might radiation therapy in addition to chemotherapy improve overall survival of patients with non-oligometastatic Stage IV non-small cell lung cancer?: Secondary analysis of two prospective studies

Abstract: BackgroundThe role of radiation therapy in addition to chemotherapy has not been well established in non-oligometastatic Stage IV non-small cell lung cancer (NSCLC). We aimed to investigate overall survival (OS) of non-oligometastatic Stage IV NSCLC treated with chemotherapy with concurrent radiation to the primary tumor.MethodsEligible patients were screened from two prospective studies. Oligometastatic and non-oligometastatic NSCLC were defined as having < 5 and ≥5 metastatic lesions, respectively. Prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…13 Thus, radical treatment of extensive metastatic NSCLC might also improve prognosis in select cases. For example, we found that radiation treatment in patients with two or more organ metastases, which most likely indicates extensive metastases, 31 also leads to better OS and CSS. Palliative TRT was also shown to be safe and might be beneficial for metastatic NSCLC patients with controlled extra-thoracic diseases.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…13 Thus, radical treatment of extensive metastatic NSCLC might also improve prognosis in select cases. For example, we found that radiation treatment in patients with two or more organ metastases, which most likely indicates extensive metastases, 31 also leads to better OS and CSS. Palliative TRT was also shown to be safe and might be beneficial for metastatic NSCLC patients with controlled extra-thoracic diseases.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, radical treatment of extensive metastatic NSCLC might also improve prognosis in select cases. For example, we found that radiation treatment in patients with two or more organ metastases, which most likely indicates extensive metastases, also leads to better OS and CSS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The researchers also reported that LCT was associated with a significantly longer time to appearance of new lesions. On the basis of these results, LCT appears to have a role in the management of oligometastatic stage IV NSCLC, in addition to traditional systemic therapy, although it is important to note that these data were derived from a few studies in American and French populations (Gomez et al 2019;Rusthoven et al 2009;Su et al 2016;Zhang et al 2018). Given the regional and ethnic differences in NSCLC cases, further studies are needed to confirm that LCT does indeed have a good efficacy, with acceptable side effects, in other populations.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study showed that treatment of IV NSCLC with joint administration of four to five cycles of chemotherapy and three-dimensional radiotherapy may prolong survival especially for patients with single metastatic sites [22][23][24]. However, the role of chemotherapy given concurrently with primary tumor radiotherapy for stage IV squamous NSCLC patients is not well-defined, and the independent prognostic factors for OS in stage IV squamous NSCLC patients treated with concurrent chemoradiotherapy remains to be answered.…”
mentioning
confidence: 99%